2022
DOI: 10.3389/fphar.2022.969207
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect and mechanism of combination therapy with ursolic acid and insulin on diabetic nephropathy in a type I diabetic rat model

Abstract: This work aims to investigate the therapeutic effect of ursolic acid (UA) plus insulin (In) on diabetic nephropathy (DN) in streptozotocin (STZ)-induced T1DM rats. The experimental groups and operational details are as follows: A total of thirty-two SD rats were divided into four groups: the DN model group (DN, n = 8), DN + In treatment group (DN + In, n = 8), DN + In + UA administration group (DN + In + UA, n = 8), and negative control group (control, n = 8). After 8 weeks, changes in renal function indices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Based on previous experience and pre-experiments, the Type I Diabetes mellitus (T1DM) model was induced by a single intraperitoneal injection of strepotozotocin (STZ, 65 mg/kg, in 0.1 mol/L sodium citrate buffer, pH 4.4; Sigma, United States) in SD rats, and the normal control group was injected with an equal volume of citrate buffer at the same time. After 72 h of STZ injection, animals with random blood glucose levels ≥16.7 mmol/L were considered successful in modeling [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous experience and pre-experiments, the Type I Diabetes mellitus (T1DM) model was induced by a single intraperitoneal injection of strepotozotocin (STZ, 65 mg/kg, in 0.1 mol/L sodium citrate buffer, pH 4.4; Sigma, United States) in SD rats, and the normal control group was injected with an equal volume of citrate buffer at the same time. After 72 h of STZ injection, animals with random blood glucose levels ≥16.7 mmol/L were considered successful in modeling [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…T helper cell (Th17) plays an important role in the pathogenesis of lupus nephritis [108]. Research has demonstrated that, in mice with pristane-induced lupus nephritis, treatment with OA reduces dsDNA levels, IL-17A expression and interferon γ (IFN-γ), and alleviate (↑) and (↓) signs show positive and negative effects of oleanolic acid and its analogues on its target molecules, respectively In vivo CP-induced nephrotoxicity in Wistar rats UA (5, 10 mg/kg) GSH↑, SOD↑, CAT↑, MDA↓, IL-1β↓, IL-6↓, TNF-α↓, Caspase-3↓, Caspase-9↓ [141] In vivo STZ-induced DN in SD rats UA (50 mg/kg) TNF-α↓, IL-1β↓, IL-6↓, SOD↑, MDA↓, GSH↑, CAT↑, NO↓, FN↓, E-cad↑, MMP-9↑,TIMP-1↓, α-SMA↓, TGF-β1↓,SMA3↓, SMA7↓, P38↓ [167] In vivo RIRI in SD rats OA (50 mg/kg) PI3K↓, p-AKT↓, PDK1↑, p27↑, TRAP1↑, CypD↓ [168] In vitro HK-2 cells stimulated with OTA OA (2 μM) Bax↓, Bcl-2↑, Cyt-C↓, Caspase-9↓,Caspase-3↓, GRP78↓, CHOP↓ [169] In vivo STZ-induced DN in SD rats OA (50, 100 mg/kg) nephrin↑, CD68↓, COL-IV↓, p-AMPK/ AMPK↑, PGC-1α↑, TLR4↓, NF-κB↓, TGF-β1↓ [103] In vivo STZ-induced DN in SD rats OA (50 mg/kg) Caspase-3↓, Bax↓, CD31, E-cadherin↑, α-SMA↓, Vimentin↓, TGF-β1↓, p-P38↓, FGFR1↑, SIRT3↑, DPP-4↓ [170] In vivo UUO in SD rats UA (40 mg/kg) TGF-β1↓, Keap1↓, Nrf2↑, HO-1↑, 8-oxo-dG↓, Caspase-3↓, Caspase-8↓ [171] In vivo TAA-induced AKI in BALB/c mice OA (45, 90 mg/kg) MDA ↓, NOx ↓, GSH↑, SOD↑, NF-κB↓, TNF-α↓, Bax↓, Bcl2 ↑, Caspase-3↓ Nrf2↑, HO-1↑ [143] In vitro HK-2 cells stimulated with OTA UA (4 μM) Lonp1↑, Sig-1R↑, GRP78↓, p-ERK↓, p-eIF2α↓, CHOP↓, IRE1α↓, Bcl2↑, Bax↓ [142] renal injury by decreasing the deposition of IgG and IgM in the glomeruli [20]. Further studies have revealed that OA inhibits the differentiation of Th17 cells in vitro.…”
Section: Type Of Study Cell/animal Model Drug and Dose Targets Refere...mentioning
confidence: 99%
“…Diabetic kidney disease (DKD) stands as one of the most severe complications of diabetes and has emerged as the primary cause of end-stage renal disease (ESRD) globally [ 1 ]. Recent research has found that the pathogenesis of DKD involves several factors, including the downregulation of endothelial cell glucocorticoid receptor leading to epithelial-mesenchymal transition (EMT) [ 2 ], abnormal activation of the Wnt signaling pathway [ 3 ], the TGF-β signaling pathway [ 4 ], and dipeptidyl peptidase-4 (DPP-4)-mediated signaling mechanism [ 5 , 6 ], while some drugs such as angiotensin-converting enzyme inhibitors (ACEi), angiotensin receptor blocker (ARB), and sodium-glucose co-transporter-2 (SGLT2) inhibitors, as well as mineralocorticoid receptor antagonist finerenone [ 7 ], have been used in efforts to slow the progression of DKD or improve renal function, but existing therapies have not effectively halted the advancement of DKD. This lack of progress leaves 20%-40% of individuals in need of renal transplantation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%